A Study of the Philosophical Foundations, Academic Principles, and Curriculum Policy of Early Childhood Education - Lely Widorini Kurniawati; Rachma Hasibuan; Mallevi Agustin Ningrum (Jurnal Penelitian Pendidikan IPA, 2026)
This study aimed to analyze the philosophical foundations, academic underpinnings, and policy directions of Early Childhood Education (ECE) curriculum in China and compared them with Indonesia’s ECE framework. The study employed a systematic literature review approach to identify and synthesize scholarly sources, policy documents, and international academic publications related to early childhood education. The review process involved the stages of identification, selection, extraction, and synthesis of literature through thematic analysis and a comparative framework. The findings indicated that China’s ECE curriculum was rooted in Confucian, Taoist, and Buddhist values that emphasized morality, social harmony, and emotional balance. Educational reform under China Education Modernization 2035 strengthened the integration of traditional values with pedagogical innovation and promoted play-based learning. In contrast, Indonesia’s ECE curriculum was grounded in Ki Hajar Dewantara’s philosophy and Pancasila values, which highlighted learner autonomy and holistic character development. The comparative analysis revealed that both countries faced distinct challenges: China dealt with early academic pressure and disparities in teacher quality, while Indonesia focused on improving teacher competence and equitable learning facilities. The study conclusion that the successful implementation of ECE curricula depended on policy consistency, professional teacher development, and collaboration between schools and families